2021
DOI: 10.1111/andr.13076
|View full text |Cite
|
Sign up to set email alerts
|

Spermatozoa retrieval in azoospermia and expression profile of JMJD1A, TNP2, and PRM2 in a subset of the Karachi population

Abstract: Background:The difficulties encountered in surgical spermatozoa retrieval for intracytoplasmic sperm injection procedure in azoospermic men have stressed the dire need for a robust biomarker for the prediction of spermatozoa retrieval. Data have highlighted the role of JMJD1A (Jumonji domain-containing 1A), a histone H3K9 demethylase, and other nuclear proteins, protamines (PRM) and transition nuclear proteins (TNP), as biomarkers in male infertility.Objective: To access successful spermatozoa retrieval at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
(57 reference statements)
0
6
0
1
Order By: Relevance
“…ssq-1 is closely related to the genes of heat shock protein family A, of which heat shock protein HSPA2 (a gene homologous to mouse Hspa2) is an important biomarker for the detection of male infertility. 31 gsp-3 is homologous to human and mouse PPP1CA(Ppp1ca), and serine/threonine protein phosphatase (PPPs) is involved in the regulation of sperm overactivity. Therefore, these two hub genes were selected as biomarkers to detect reproductive damage induced by ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…ssq-1 is closely related to the genes of heat shock protein family A, of which heat shock protein HSPA2 (a gene homologous to mouse Hspa2) is an important biomarker for the detection of male infertility. 31 gsp-3 is homologous to human and mouse PPP1CA(Ppp1ca), and serine/threonine protein phosphatase (PPPs) is involved in the regulation of sperm overactivity. Therefore, these two hub genes were selected as biomarkers to detect reproductive damage induced by ionizing radiation.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, maintaining a stable ratio of PRM2 and PRM1 is important to protect the stability of spermatozoon DNA and to reduce the impact of oxidative stress [ 36 , 37 ]. In our study, it was shown that PRM2 plays an important role in the cryopreservation of testicular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…TNPs aid the remodelling of chromatin structure [77]. Studies have shown that mouse null mutants for either TNP1 or TNP2 became subfertile [79,80], while Zhao et al (2004) reported that mice that lack both TNPs became infertile [81]. A study was carried out on TNP1 and TNP2 gene sequencing from blood samples of 282 sterile men, 270 men with TNP1 deficiency and 266 proven fertile men [78].…”
Section: Transient Nuclear Proteins (Tnps)mentioning
confidence: 99%